King Djeḥuty-em-ḥat in Swansea: Three model scribal palettes in the collection of the Egypt Centre of Swansea University - Troy Sagrillo (A true scribe of Abydos: Essays on first millennium Egypt in honour of Anthony Leahy., 2017)
Publication of three ancient Egyptian scribal palettes from the collection of the Egypt Centre of Swansea University. One had the only known depiction of the King Djehuty-em-hat (Thothemhat) of al-Ashmunayn (Hermopolis), a little-known Upper Egyptian ruler from the late Third Intermediate Period. Chronological issues are considered.